The Nature of Long-term Temporary Marriage in Imamiah Jurisprudence and Legal System - R. Mahdi, H. Shafiei Fini, (Opción, 2019)
The study aims to investigate the nature of long-term temporary marriage in Imamiah jurisprudence and the legal system via a comparative qualitative research method. As a result, the famous saying of jurisprudence is also that the marriage is temporary, and that adultery is famously known to be less bug-free than in the non-celebrated, while in the jurisprudence it is doubly and irrevocable. In conclusion, after the marriage contract is concluded, the principle of its validity is valid, secondly, with the void of this contract, many corrupt sequences, including the raising of illegitimate children, will be inevitable.